Central bank liquidity policy in modern times - Skylar Brooks (Bank of Canada, 2024)
Central banks play a crucial role in promoting financial stability. They act as financial system stabilizers through their capacity to create liquidity and channel it to financial institutions and markets in times of stress - a role that has evolved and expanded substantially over the past 15 years. This paper provides a stylized discussion of recent policy developments in this area and what they mean for debates and decisions about the design of central bank liquidity policy. Across several policy dimensions, the paper outlines broad changes since the 2008-09 global financial crisis and highlights some of the key challenges, choices and considerations facing the designers of central bank liquidity tools today.
Keywords: D53; E58; E61; G01; G2; G21; G23; H12; 330; Lender of last resort; Financial stability; Central bank research; Financial institutions; Financial markets